Otoritas Majelis Pembinaan dan Pengawasan Daerah terhadap Pelanggaran Etika yang Dilakukan oleh Pejabat yang Bertugas dalam Pembuatan Akta Tanah - Huda, Miftahul; Suhaini, Ani (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2024)
This study aims to analyze the implementation of PPAT (Pejabat Pembuat Akta Tanah) guidance and supervision. It utilizes a normative and descriptive approach, gathering primary and secondary data through field investigations and relevant material collection. The analysis is qualitative, revealing that the PPAT Supervisory Council (PPAT) MPPD (Masyarakat Perlindungan Pejabat Dokumen) plays an active role in addressing non-compliance with office hours, in accordance with Article 47 of Permen ATR/Ka BPN No. 2 of 2018. Sanctions for such violations include written warnings and higher-level discussions with MPPW (Masyarakat Perlindungan Pejabat Wilayah). To improve guidance and supervision, efforts include disseminating land policies, defining PPAT duties, and regular office oversight. This study highlights the importance of effective supervision in ensuring PPAT compliance with regulations and duties, ultimately contributing to improved land management.